Animal laws of India - India; Gandhi, Maneka; Husain, Ozair; Panjwani, Raj (Delhi : Universal Law Pub., 2006)
Compilation of central and state laws
Keywords: Animal welfare -- Law and legislation -- India; Animal welfare -- Law and legislation -- India -- States